2020
DOI: 10.1038/s41467-020-16628-4
|View full text |Cite
|
Sign up to set email alerts
|

Contactless probing of polycrystalline methane hydrate at pore scale suggests weaker tensile properties than thought

Abstract: Methane hydrate is widely distributed in the pores of marine sediments or permafrost soils, contributing to their mechanical properties. Yet the tensile properties of the hydrate at pore scales remain almost completely unknown, notably the influence of grain size on its own cohesion. Here we grow thin films of the hydrate in glass capillaries. Using a novel, contactless thermal method to apply stress, and video microscopy to observe the strain, we estimate the tensile elastic modulus and strength. Ductile and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 65 publications
4
24
0
Order By: Relevance
“…Most filaments were spiralled, with a typical pitch of 10-15 µm, some completing a dozen or more turns before terminating in a club head or mass of small turns. Interestingly, the halo of gas hydrate, commonly observed on glass substrates [35,45], was not prominent at this stage. Instead, circular hydrate halos appeared that were centred on, and radiating around, the points of contact of the filaments drooping onto the glass floor of the cell (Figure 4b,c).…”
Section: Growth Of Hydrate Filamentsmentioning
confidence: 83%
See 3 more Smart Citations
“…Most filaments were spiralled, with a typical pitch of 10-15 µm, some completing a dozen or more turns before terminating in a club head or mass of small turns. Interestingly, the halo of gas hydrate, commonly observed on glass substrates [35,45], was not prominent at this stage. Instead, circular hydrate halos appeared that were centred on, and radiating around, the points of contact of the filaments drooping onto the glass floor of the cell (Figure 4b,c).…”
Section: Growth Of Hydrate Filamentsmentioning
confidence: 83%
“…The grains were covered in a few minutes by a dense growth of filaments of methane hydrate extending into the gas, similar to the observations by Servio and Englezos [33], who observed filaments growing into the gas from a hydrate crust on a droplet of water under large enough supercooling. (See also Atig et al [45], who observed MH filaments growing on the methane side from the hydrate crust separating the water and gas compartments in a thin glass capillary). Within a few minutes, filaments with typical lengths of up to several hundred micrometers over curves-corresponding to a growth rate of a few micrometers per second-formed and grew from their extremity in the gas phase (see Discussion below).…”
Section: Growth Of Hydrate Filamentsmentioning
confidence: 94%
See 2 more Smart Citations
“…2C, magenta circles; see also refs. 29 and 30) and is likely controlled by the local pressure difference and crust tensile strength (47)(48)(49)(50). The location of the thinnest crust corresponds to weaker tensile strength and, thus, is more prone to rupture.…”
Section: Significancementioning
confidence: 99%